2016
DOI: 10.1007/s11682-016-9614-6
|View full text |Cite
|
Sign up to set email alerts
|

Default mode network activity and neuropsychological profile in male children and adolescents with attention deficit hyperactivity disorder and conduct disorder

Abstract: It is known that patients with Attention Deficit and Hyperactivity disorder (ADHD) and Conduct disorder (CD) commonly shows greater symptom severity than those with ADHD alone and worse outcomes. This study researches whether Default mode network (DMN) is altered in adolescents with ADHD + CD, relative to ADHD alone and controls or not. Ten medication-naïve boys with ADHD + CD, ten medication-naïve boys with ADHD and 10-age-matched typically developing (TD) controls underwent functional magnetic resonance imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
1
16
0
2
Order By: Relevance
“…Cikili-Uytun et al found that increased DMN activity in ADHD+CD group compared to ADHD and in the ADHD group compared to controls in several DMN regions. This result is consistent with rs-fMRI studies, which showed that the increased DMN with ADHD but diferent from the study which showed decreased DMN activity with CD adolescents [91]. Increased activity in the DMN was present in some previous studies, and this study is consistent with the hypothesis that ADHD individuals may have increased disturbances during task performance and that relect faulty deactivation of the DMN [92].…”
Section: Neurobiological Factorssupporting
confidence: 91%
“…Cikili-Uytun et al found that increased DMN activity in ADHD+CD group compared to ADHD and in the ADHD group compared to controls in several DMN regions. This result is consistent with rs-fMRI studies, which showed that the increased DMN with ADHD but diferent from the study which showed decreased DMN activity with CD adolescents [91]. Increased activity in the DMN was present in some previous studies, and this study is consistent with the hypothesis that ADHD individuals may have increased disturbances during task performance and that relect faulty deactivation of the DMN [92].…”
Section: Neurobiological Factorssupporting
confidence: 91%
“…Other recent studies have also reported reduced DMN rsFC in male adolescents with CD compared to healthy controls (Zhou et al, 2016). Higher ADHD scores, however, related to increased rsFC density and alterations (Lu, Zhou, Zhang, et al, 2017;Pu et al, 2017;Uytun et al, 2016) in DMN areas. Critically, these rs-fMRI studies were mostly limited to male adolescents with CD, and further distinct manifestations of aggression including reactive and proactive aggression (RA/PA) (Dodge & Coie, 1987) largely neglected.…”
Section: Introductionmentioning
confidence: 75%
“…After Fisher's transformation to normally distributed z-scores, general linear model (GLM) analyses were computed. Second-level analysis included random-effects analysis of covariance for group comparisons, with further analyses adding ADHD symptoms as additional covariates of no interest based on previous reports on the importance of considering ADHD symptoms to differentiate rsFC of cases and controls (Broulidakis et al, 2016;Uytun et al, 2016). Linear regressions separately tested the association between RA and PA and CU total score and dimensions on rsFC within cases.…”
Section: Functional Connectivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that abnormalities in the intrinsic activity of resting state networks may contribute to the etiology of conduct disorder and poor prognosis of ADHD in combination with conduct disorder (Uytun et al, 2016) [15]; whereas reduced default mode functional connectivity is associated with expressions of conduct disorder (Broulidakis et al, 2016) [16], individuals presenting ADHD present disproportionately high expressions of default mode network activity related to goal-directed tasks accompanied by 'switch-specificity alterations in the right insula region (Sidlauskaite et al, 2016) [17]. Moreover, adult ADHD patients demonstrated markedly stronger resting-state functional connectivity in the anterior cingulate gyrus of the executive control network, as well as in the cerebellar network, than healthy control adults (Moster et al, 2016) [18].…”
mentioning
confidence: 99%